Theory and Practice of Modern Domestic Preschool Education - Burlakova I. A. (Moscow State University of Psychology and Education, 2015)
The author marked the most important theoretical principles of cultural-historical psychology and activity approach, which underlie the educational standard. The idea of inherent value of childhood, the position of the amplification and the need to take into account the child's age are fundamental for preschool education.